Modeling of rotary desiccant wheels - Harshe, Yogesh M.; Utikar, R. P.; Ranade, V. V.; Pahwa, D. (Chemical Engineering & Technology, 2005)
Rotary desiccant wheels are widely used in dehumidification and energy recovery applications. In this work, we have developed a 2D, steady state model of a rotary desiccant wheel. Mass and energy balance equations for the air streams and the desiccant wheels were developed. The hydraulic diameter and surface area for heat and mass transfer were calculated based on knowledge of the flute geometry. Appropriate correlations for the Sherwood number and Nusselt number were used to estimate heat and mass transfer coefficients. The model is capable of predicting steady state behavior of desiccant wheels having at the most three sections (process, purge, and regeneration). The mathematical model was validated using a real desiccant wheel, and the calculation results are in reasonable agreement with the experimental data. Based on this model, the temperature and humidity profiles in the wheel during both the dehumidification and the regeneration processes are analyzed. The simulated results were used to gain an insight into the operation of desiccant wheels. The model and the presented results will be useful for optimizing dehumidification and energy recovery applications.
Keywords: 1; 4-benzodioxan-2-carboxylate; 4-benzodioxan-2-carboxylic acid; doxazosin; enantio selectivity; enantiomeric ratio; ethyl 1; ethyl acetate; Lipases; transesterfication

Novel enzymatic route for kinetic resolution of (+/-)1,4-benzodioxan-2-carboxylic acid - Kasture, Sangita M.; Varma, R; Kalkote, Uttam R.; Nene, S; Kulkarni, Bhaskar D. (Biochemical Engineering Journal, 2005)
Ethyl 1,4-benzodioxan-2-carboxylate is used as an intermediate compound for the production of drug doxazosin mesylate. The title compound was kinetically resolved to get S-enantiomer of ethyl 1,4-benzodioxan 2-carboxylate in a simple lipase catalyzed transesterificafion reaction. Ethyl acetate was used as reaction medium as well as acyl donor. The influence of the enzyme source and time of reaction on the enantio selectivity of product were studied. Lipase from Candida antartica-B (Novozyme A/S) catalyzed transesterification reaction with good enantio selectivity towards S-enantiomer. The high enantiomeric ratio, E= 160, provided S-2 an acceptable chemical yield (50%) and enaritiomeric excess (>95%). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 1; 4-benzodioxan-2-carboxylate; 4-benzodioxan-2-carboxylic acid; doxazosin; enantio selectivity; enantiomeric ratio; ethyl 1; ethyl acetate; Lipases; transesterfication

Synthesis of ethyl acetate by esterification of acetic acid with ethanol over a heteropolyacid on montmorillonite K10 - Gurav, Hanumant; Bokade, Vijay V. (Journal of Natural Gas Chemistry, 2010)
In present work, liquid phase esterification of acetic acid with ethanol over dodecatungestophosphoric acid (DTPA) supported on K10 mommorillonite was systematically studied and optimization of process parameters was carried out The 20% m/m urpAtK tO was found to be the optimum catalyst with 90% acetic acid conversion and 100% ethyl acetate selectivity The study was also explored to see the feasibility of 20% m/m DTPA/K10 as a catalyst for the alkylation of acetic acid with other alcohols like methanol, iso-propanol and sr-butanol. The 20% m/m DTPA/K10 has shown increased activity with the increase in carbon number, at the same alcohol reflux The results are novel
Keywords: Acetic acid; Ethanol; ethyl acetate; Heteropolyacid; montmorillonite K10

Experimental analysis of vapour-liquid phase equilibria for binary systems of diethyl carbonate with methyl, ethyl, isopropyl, n-butyl and isoamyl acetates at 95 kPa - Bhoi, Bharat R.; Mali, Nilesh A.; Joshi, Sunil S. (Journal of Chemical Thermodynamics, 2020)
Experimental analysis of vapour-liquid phase equilibrium (VLE) for five binary pairs of diethyl carbonate (DEC) with methyl acetate, ethyl acetate, isopropyl acetate, n-butyl acetate and isoamyl acetate was carried out in this study. VLE data were generated experimentally at local atmospheric pressure of 95 kPa in a glass dynamic recirculation still. Reliability of data was checked with the thermodynamic consistency tests by Van Ness, infinite dilution, pure component and mean absolute deviation test. Experimental data was found to be thermodynamically consistent with all tests and data was regressed with Wilson, NRTL and UNIQUAC activity coefficient models to determine binary interaction parameters. Binary pair of DEC with n-butyl acetate has shown azeotropic behaviour with minimum boiling azeotrope and a close boiling behaviour through-out the composition range. No azeotropic behaviour was observed for the rest of the binary pairs. (c) 2020 Elsevier Ltd.
Keywords: Diethyl carbonate; ethyl acetate; Isobaric; Isopropyl acetate; methyl acetate; VLE